The effect of mind mapping-based learning model on listening skills - Elisabet Janul (Universitas Pendidikan Indonesia, 2024)
Several skills need to be mastered in the 21st century, one of which is communication. Good and correct communication will be formed if an individual masters four important language components. These components are listening, speaking, reading, and interrelated writing skills. This study tried to reveal the results of students' listening skills by using mind-mapping media during classroom learning. The approach used in this research is descriptive qualitative. The data collection techniques used in this research are observation, interview, and documentation. The subjects of this study were homeroom teachers and elementary school students. Data analysis techniques include data reduction, data display, and data verification. The research results show that using creative and innovative models can develop students' language skills. Learning media using mind-mapping media has improved students' listening skills. Of course, various efforts will continue to be made to create a 21st-century generation skilled in communicating properly and correctly. Abstrak Terdapat beberapa keterampilan yang perlu dikuasai dimiliki di abad 21, salah satunya yaitu komunikasi. Komunikasi yang baik dan benar akan terbentuk jika seorang individu menguasai empat komponen penting dalam berbahasa. Komponen tersebut yaitu keterampilan menyimak, berbicara, membaca dan menulis yang saling berkaitan satu sama lain. Pada penelitian ini mencoba mengungkapkan hasil keterampilan menyimak peserta didik dengan menggunakan media mind mapping saat pembelajaran di kelas. Pendekatan yang digunakan dalam penelitian ini yaitu deskriptif kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Subjek penelitian ini adalah guru wali kelas dan peserta didik sekolah dasar. Teknik analisis data meliputi reduksi data, display data, dan verifikasi data. Hasil dari penelitan menunjukkan bahwa penggunakan model yang kreatif dan inovatif dapat mengembangkan keterampilan berbahasa peserta didik. Penggunaan media pembelajaran menggunakan media mind mapping telah terbukti dapat meningkatkan keterampilan menyimak peserta didik. Tentunya berbagai upaya akan terus dilakukan supaya mencapai target menciptakan generasi abad 21 yang terampil berkomunikasi dengan baik dan benar. Kata Kunci: keterampilan menyimak; model pembelajaran berbasis proyek; sekolah dasar